Substantiation of the technological process for mechanical processing of roller unit parts of conveyors as a factor influencing the efficiency of their operation - L.P. Kalafatova; M.O. Babenko; S.O. Virich (Технічна інженерія, 2025)
Technological cost is a key indicator of product competitiveness; therefore, the ability to manufacture high-quality and precise components at a low production cost contributes to the overall advancement of a mechanical engineering enterprise. The main approaches to regulating technological cost include reducing the following: machining time for a component, downtime of selected equipment, tool costs and its reconditioning expenses, as well as the time required for tool changeover and reconfiguration.